Quests aside. Volume 1 - Schirmer, Brian (Vault Comics, 2023)
"A skeleton, an apprentice mage, and an exiled princess walk into a bar... for another shift at Quests Aside, the local watering hole run by once legendary, now retired, adventurer Barrow. When the King privately explains that he plans to shut the place down, Barrow must find a way to hold onto his business, the friendships, and the family he's built around it"--Back cover.